2017
DOI: 10.1007/s10554-017-1067-5
|View full text |Cite
|
Sign up to set email alerts
|

Selective anti-scatter grid removal during coronary angiography and PCI: a simple and safe technique for radiation reduction

Abstract: Objectives The aim of this study was to quantify the radiation dose reduction during coronary angiography and percutaneous coronary intervention (PCI) through removal of the anti-scatter grid (ASG), and to assess its impact on image quality in adult patients with a low body mass index (BMI). Methods A phantom with different thicknesses of acrylic was used with a Westmead Test Object to simulate patient sizes and assess image quality. 129 low BMI patients underwent coronary angiography or PCI with or without th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Roy et al . [26] reported a 47% reduction in radiation dose to the patient as well as reduced scatter to the operator with removal of the grid during coronary angiography. In pediatric cardiac catheterization, Gould et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roy et al . [26] reported a 47% reduction in radiation dose to the patient as well as reduced scatter to the operator with removal of the grid during coronary angiography. In pediatric cardiac catheterization, Gould et al .…”
Section: Discussionmentioning
confidence: 99%
“…Other fields of medicine have investigated the use of grid removal as a means of reducing patient radiation. Roy et al [26] reported a 47% reduction in radiation dose to the patient as well as reduced scatter to the operator with removal of the grid during coronary angiography. In pediatric cardiac catheterization, Gould et al [27] reported a 30% decrease in DNA double-strand breakages with grid removal.…”
Section: Discussionmentioning
confidence: 99%
“…They found reductions in radiation doses of about 50% with very little effect on image quality. They suggest a larger clinical study to assess procedural outcomes [5].…”
Section: X-ray Imagingmentioning
confidence: 99%
“…However, this perspective is not exclusive and may depend on pediatric patient size (Onnasch et al 2004, Gislason et al 2010, Ubeda et al 2013, Chamberlain et al 2019. Others have also investigated the use of non-grid or air gap techniques to mitigate scatter for adult patient fluoroscopic and angiographic imaging (Gray and Swee 1982, Partridge et al 2006, Cortis et al 2014, Smith et al 2016, Roy et al 2017. Simply removing the grid results in reduced patient radiation dose due to the combination of automatic dose rate control circuit and lack of x-ray beam attenuation by the grid.…”
Section: Introductionmentioning
confidence: 99%